Study design of 'FRIENDS for Life': process and effect evaluation of an indicated school-based prevention programme for childhood anxiety and depression - Kösters Mia P; Chinapaw Mai JM; Zwaanswijk Marieke; van der Wal Marcel F; Utens Elisabeth MWJ; Koot Hans M (BMC, 2012)
Abstract Background Anxiety disorders and depression are highly prevalent in children and affect their current and future functioning. 'FRIENDS for Life' is a cognitive-behavioural programme teaching children skills to cope more effectively with feelings of anxiety and depression. Although 'FRIENDS for Life' is increasingly being implemented at Dutch schools, its effectiveness as a preventive intervention in Dutch schools has never been investigated. The aim of the study is to evaluate the effectiveness of 'FRIENDS for Life' as an indicated school-based prevention programme for children with early or mild signs of anxiety or depression. Methods/Design This study is a controlled trial with one pre-intervention and three post-intervention measurements (directly after, and 6 and 12 months after the end of the programme). The study sample consists of children aged 10-12 years (grades 6, 7 and 8 of Dutch primary schools), who show symptoms of anxiety or depressive disorder. Data are collected through self-report, teacher report and peer nomination. A process evaluation is conducted to investigate programme integrity (whether the programme has been executed according to protocol) and to evaluate children's and parents' opinions about 'FRIENDS for Life' using online focus groups and interviews. Discussion The present study will provide insight into the effectiveness of 'FRIENDS for Life' as an indicated school-based prevention programme for children with early or mild signs of anxiety or depression. Trial registration Netherlands Trial Register (NTR): NTR2397